EFFECT OF FAST FOOD CONSUMPTION WITH OBESITY OCCURRENCE OF TEENAGER IN INDRAMAYU - Depi Yulyanti; Muhamad Fauzi; Heri Sugiarto; Rudiansyah Rudiansyah; Riski Andriyani (SEKOLAH TINGGI ILMU KESEHATAN (STIKes) INDRAMAYU, 2021)
Fast food is characterized by an imbalanced nutritional content. Most are high in calories, but very low in fiber. Fast food is a major factor affecting obesity. Based on the 2013 Riskesdas the prevalence of obesity was 28.9%, while the results of the 2018 Riskesdas data showed that the prevalence of obesity had reached 52.8%. Based on these data, it is known that there is an increase in obesity cases by 1.36%. The purpose of this study was to determine the relationship between fast food consumption and obesity in adolescents. This research method uses analytical research design with a cross sectional approach. The sampling technique used accidental sampling with a total of 94 samples calculated using the Slovin formula. The research instrument used a questionnaire, research sites in vocational high schools in Indramayu District in 2019. The analysis used univariate and bivariate analysis was carried out by using the Chi-Square Test. The results of this study indicate that there is an effect between consumption of fast food and the incidence of obesity with a value of P = 0.000. The next researcher should examine family support and the school environment for fast food consumption behavior in teenagers.